Filaricidal effect of 4 (5-nitrofuryl-2)-methylene amino compounds - XI Yu-rui; XU Yu-xin; NIE Jin-hua; YAN Min; ZHANG Zhen (Acta Pharmacologica Sinica, 2016)
Filaricidal effect of 3 nitrofutans, M 254 (1-[(5-nitrofuryl-2)-methylene amino] – imidazolin-2-one), M279 (1-[(5-nitrofuryl-2)-methylene amino]-tetrahydropyrimidin-2-one methanol propionate) and M280 (1-[(5-nitrofuryl-2)-methylene amino]-tetrahydropyrimidin-2-one methanol cyclohexanocarboxylate) were compared with that of furapyrimidone (M 170)(1-[(5-nitrofuryl-2)-methylene amino] tetrahydropyrimidin-2-one). In mice the acute oral LD50 and 95%confidence limits of M254, M279, M280 and M170 were 556±85, 556±88, 730±122 and 231±21 mg/kg, respetively. The efficacy of M254 on Litomosoides carinii in cotton rats was superior to that of M170 on equitoxic basis; all adult worms in the pleural cavity were killed when M254 was given orally to L. carinii infected cotton rats at 1/40 LD50 daily for 5 consecutive days while M170 failed to do so even at 1/20 LD50 level. M254 was also more effective than M170 against microfilariae in peripheral blood & peritoneal cavity of Mongolian jirds infectcd with Brugia malayi, though the 2 compounds were similar in their effects on adult worms in jird as well as microfilariae and adult worms in vitro. Both M 279 and M 280 were inferior to M 170 in their filaricidal effect.